2010
DOI: 10.3399/bjgp10x515395
|View full text |Cite
|
Sign up to set email alerts
|

Are patients with dementia treated as well as patients without dementia for hypertension, diabetes, and hyperlipidaemia?

Abstract: BackgroundPatients suffering from dementia are at risk of being treated differently by GPs from patients without it. Explanations for this could be stigmatisation, treatment with a palliative approach, and the result of the disease process. AimTo ascertain whether patients with dementia are treated differently, the index diseases of hypertension, diabetes, and hyperlipidaemia were used to measure care. Design of studyRetrospective matched control study. SettingGerman general practice. MethodSixteen GP practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“… Reported differences in care/treatment Connolly [92]UKDM, StrokeCross sectional700 PWD (compared to people without dementia on QOF register)Monitoring and treatmentYesPWD -significantly lower on 73% of QOF indicators; including peripheral pulses check, neuropathy testing, cholesterol measures for stroke.Curtis [33]USAVI (AMD)Retrospective cohort284380TreatmentYesPWD significantly less likely to receive anti-VEGF RR 0.88 (95% CI 0.88 to 0.89)Guijarro [45]SpainVI, generalCohort40482TreatmentYesPWD had some procedures less frequently than those without dementia. For example,cataract surgery ( P <0.001), hernia repair, orthopaedic surgeryKeenan [11]UKVI (AMD)Cohort65894 (AMD cohort, 168092 dementia cohort)TreatmentYesPWD significant decrease in likelihood of hospital admission for AMD P <0.001Löppönen [55]FinlandVI, generalCross sectional (survey)1260 older people (112 PWD)Diagnosis and treatmentYesPWD -more undiagnosed diseases compared to those without dementia ( P =0.041) , less likely to be diagnosed with glaucoma ( P =0.022)Müther [60]GermanyDM, hypertensionRetrospective matched control216 PWD, 216 matched controlsTreatmentNoNo significant differences in treatment for those with and without dementia. PWD more likely not to receive medication for hypertension or be treated with low-priced medications (not significant)Saposnik [66]CanadaStrokeCohort877 with pre-existing dementiaTreatmentYesPatients with pre-existing dementia less likely to receive intravenous thrombolysis.877 controls (no pre-existing dementia)Sloan [69]USAAcute MICross sectional5851 admitted for AMI with dementia, 123241 admitted for AMI without dementiaTreatmentYesPWD less likely to have a range of invasive procedures compared to those without a history of dementiaThorpe [74]USADM, VICohort288805 (44717 PWD)MonitoringYesPWD less likely to receive HbA1c tests (73% ver...…”
Section: Resultsmentioning
confidence: 99%
“… Reported differences in care/treatment Connolly [92]UKDM, StrokeCross sectional700 PWD (compared to people without dementia on QOF register)Monitoring and treatmentYesPWD -significantly lower on 73% of QOF indicators; including peripheral pulses check, neuropathy testing, cholesterol measures for stroke.Curtis [33]USAVI (AMD)Retrospective cohort284380TreatmentYesPWD significantly less likely to receive anti-VEGF RR 0.88 (95% CI 0.88 to 0.89)Guijarro [45]SpainVI, generalCohort40482TreatmentYesPWD had some procedures less frequently than those without dementia. For example,cataract surgery ( P <0.001), hernia repair, orthopaedic surgeryKeenan [11]UKVI (AMD)Cohort65894 (AMD cohort, 168092 dementia cohort)TreatmentYesPWD significant decrease in likelihood of hospital admission for AMD P <0.001Löppönen [55]FinlandVI, generalCross sectional (survey)1260 older people (112 PWD)Diagnosis and treatmentYesPWD -more undiagnosed diseases compared to those without dementia ( P =0.041) , less likely to be diagnosed with glaucoma ( P =0.022)Müther [60]GermanyDM, hypertensionRetrospective matched control216 PWD, 216 matched controlsTreatmentNoNo significant differences in treatment for those with and without dementia. PWD more likely not to receive medication for hypertension or be treated with low-priced medications (not significant)Saposnik [66]CanadaStrokeCohort877 with pre-existing dementiaTreatmentYesPatients with pre-existing dementia less likely to receive intravenous thrombolysis.877 controls (no pre-existing dementia)Sloan [69]USAAcute MICross sectional5851 admitted for AMI with dementia, 123241 admitted for AMI without dementiaTreatmentYesPWD less likely to have a range of invasive procedures compared to those without a history of dementiaThorpe [74]USADM, VICohort288805 (44717 PWD)MonitoringYesPWD less likely to receive HbA1c tests (73% ver...…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies 98,110,117,118,123,129,136,139,145,155,161 compared access to treatment or receipt of services in groups with and without dementia. Ten 98,110,117,118,129,136,139,145,155,161 of the 11 studies found some evidence that people with dementia were less likely to receive the same quality of care or access to services as those without dementia.…”
Section: Comprehensiveness and Equitymentioning
confidence: 99%
“…23 Quality indicators -even bundled indicators that emphasise the importance of individual specific review -cannot reflect or assess the complexities of primary health care and the uniqueness of individual patients 24,25 but, rather, involve making and assessing generalisations about individual patients. The quality of a dementia review will also depend on the continuity of care, interpersonal care, and trust between health professional, patient and, where appropriate, carer.…”
Section: Strengths and Limitationsmentioning
confidence: 99%